1990
DOI: 10.1111/j.1528-1167.1990.tb06303.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxyindoleacetic Acid and Homovanillic Acid in Cerebrospinal Fluid of Children with Febrile Convulsions

Abstract: 5-Hydroxyindoleacetic acid (5-HIAA) and homovanillic acid (HVA) were measured by high-performance liquid chromatography (HPLC) in lumbar cerebrospinal fluid (CSF) obtained from febrile children subdivided according to the presence or absence of convulsions. Lumbar puncture was made either early (mean time 2 h) or late (3-6 days) after the febrile convulsion. The level of 5-HIAA was significantly decreased in children early and late after the febrile convulsion as compared with the convulsion-free group, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 21 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…The reduced KYNA/kynurenine and KYNA/3-OH-KYN ratios in epilepsy patients are in line with this neurodegeneration hypothesis. These results are indicative of an imbalance between neuroprotective and neurotoxic metabolites in epilepsy patients, and with previous reports showing significantly lower levels of neuroprotective KYNA in children with intractable epilepsy than in healthy controls [21][22][23] .…”
Section: Discussionsupporting
confidence: 66%
“…The reduced KYNA/kynurenine and KYNA/3-OH-KYN ratios in epilepsy patients are in line with this neurodegeneration hypothesis. These results are indicative of an imbalance between neuroprotective and neurotoxic metabolites in epilepsy patients, and with previous reports showing significantly lower levels of neuroprotective KYNA in children with intractable epilepsy than in healthy controls [21][22][23] .…”
Section: Discussionsupporting
confidence: 66%
“…Controversial results for HVA concentrations in the CSF in different types of epilepsy have been reported. 16,17 A decreased concentration of HVA in adults with complex partial seizures but normal in patients with generalized tonic-clonic seizures has also been described. 5 Van der Heyden et al 4 also reported a strong association between low HVA and epilepsy (the patients suffered from different types of epilepsy, many of them in combination with another neurological disorder); however, the age range of these patients was very large.…”
Section: (2) Neurological Patternmentioning
confidence: 99%
“…Both experimental and clinical observations suggest that changes in levels of 5-hydroxyindoleacetic acid (5-HIAA) and 3-methoxy-4-hydroxyphenylacetic acid [homovaniliic acid (HVA)] in the CSFand in the brain may be a biological marker of pathological brain activity. Among monoamine metabolites, 5-HIAA and HVA are changed in concentration in patients with various types of seizures (Giroud et al, 1990), obsessive-compulsive disorders (Insel et al, 1989, hepatic encephalopathy (Knell et al, 1974Jellinger et al, 1978;Moroni et al, 1986), and hypoxic brain injury after cardiac arrest (Odink et al, 1989). 5-HIAA and HVA levels were increased in a doserelated manner by 2,4-dichlorophenoxyacetic acid experimentally in rat CSF and brain (Elo and Mac-Donald, 1989).…”
mentioning
confidence: 99%